Analisis Keputusan Investasi Dan Pendanaan Eksternal Terhadap Profitabilitas Selama Pandemi Covid 19 Pada Perusahaan Tekstil Yang Terdaftar Di Bursa Efek Indonesia - Harahap, Julienda Br; Andri, Shofwan; Lubis, Farida Khairani; Sari, Ike Rukmana; Wibiansya, M Selvin (Universitas Islam Islam Sumatera Utara, 2023)
The COVID-19 outbreak has had a serious impact on almost all countries in the world, including Indonesia. The influence generated is not only in one field, but in almost all existing activities. One aspect that is of concern amid the outbreak of the Corona virus is investment. The existence of various restrictions in a country certainly has an impact on economic activity. The purpose of this study is to determine investment decisions on profitability during the covid 19 pandemic in textile companies listed on the Indonesia Stock Exchange, to determine the effect of external funding on profitability during the covid 19 pandemic in textile companies listed on the Indonesia Stock Exchange and to find out the influence of investment decisions and external funding on profitability during the covid 19 pandemic in textile companies on the Indonesia stock exchange. The company data sampled were 14 companies with a total sample of 42 from 2019 to 2021. The data used is secondary data. The sample used in this study was saturated sampling or census sampling, which is a sampling technique in which all members of the population are used as samples. This type of research used is quantitative research. The test performed is multiple linear regression analysis by first carrying out the classical assumption test which includes normality, multicollinearity, autocorrelation, and heteroscedasticity tests. This study used SPSS software version 25. The results of this study indicate that investment decisions have a positive and significant effect on profitability during the covid-19 pandemic for textile companies listed in companies listed on the Indonesia Stock Exchange, external funding has no positive and significant effect on profitability during the covid-19 pandemic for textile companies listed on the stock exchange. Infonesia Securities, investment decisions and external funding simultaneously affect profitability during the covid q9 pandemic which are listed on the Indonesia Stock Exchange